DESIGN OF PRISON SECURITY INFORMATION SYSTEM USING RFID - Purwito, Arip; Sitanggang, Dani Wijaya Fauji; Suprayitno, Suprayitno; Marbandi, Arie (Indonesian Naval Technology College - STTAL, 2018)
Information systems and technology are currently developing rapidly, so computers can beused as security tools automatically with the addition of Radio Frequency Identification (RFID)technology. Sattahti security personnel in the detention room are required to always be ready to carryout security, supervision within the scope of the detention room. So far, Sattahti personnel inconducting surveillance and guarding detainees in and out of the room still use padlock locks so thatsecurity is less than the maximum, meeting SOP standards so that some detainees have a chance toescape, so that Sattahti personnel cannot properly monitor prisoners because there is no regulatingsystem detention rooms are better IT-based. Based on the above problems, it is necessary to designand build a detention room security information system using RFID technology. So that every sattahtipersonnel can be accessed in the security system information system database of the detention room.This is very helpful for sattahti personnel in the process of guarding detainees. This system can do anautomatic lock along with the time for each personnel who bring prisoners in and out of the detentionroom, by using serial communication from a personal computer (PC) to a microcontroller (reader RFIDstater kit ID-12 LA) so that it will read the identity card (tag) RFID) every person. This detention roomsecurity information system is useful to accelerate and facilitate personnel in changing duty pickets tothe next personnel regarding the whereabouts of all the strength of the prison guard personnel atSATTAHTI.Keywords: Information on detention room security, RFID.